2009
DOI: 10.1073/pnas.0903507106
|View full text |Cite
|
Sign up to set email alerts
|

The genomic basis of trophic strategy in marine bacteria

Abstract: Many marine bacteria have evolved to grow optimally at either high (copiotrophic) or low (oligotrophic) nutrient concentrations, enabling different species to colonize distinct trophic habitats in the oceans. Here, we compare the genome sequences of two bacteria, Photobacterium angustum S14 and Sphingopyxis alaskensis RB2256, that serve as useful model organisms for copiotrophic and oligotrophic modes of life and specifically relate the genomic features to trophic strategy for these organisms and define their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
682
6
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(767 citation statements)
references
References 38 publications
55
682
6
3
Order By: Relevance
“…Despite the fact that the probes used target groups from different taxonomical ranks, most of these groups present ecological coherence (Philippot et al, 2010). Thus, our results provide valuable information concerning the auto-ecology of the most abundant bacterial large phylogenetic groups in the sea, sometimes difficult to discern in the huge amount of genomic data (for example, Lauro et al, 2009). For example, our observations reinforce previous reports that SAR11 can grow in culture only with low substrate concentration (Rappé et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite the fact that the probes used target groups from different taxonomical ranks, most of these groups present ecological coherence (Philippot et al, 2010). Thus, our results provide valuable information concerning the auto-ecology of the most abundant bacterial large phylogenetic groups in the sea, sometimes difficult to discern in the huge amount of genomic data (for example, Lauro et al, 2009). For example, our observations reinforce previous reports that SAR11 can grow in culture only with low substrate concentration (Rappé et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, largegenome copiotrophs would have higher genetic potential (more genes coding for a higher number of enzymes), allowing handling a wider range of molecules, which makes them more generalists (Lauro et al, 2009); however, they need a higher amount of energy to start the synthesis of such a complex enzymatic machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of chaperones may help bacteria to deal with low nutrient availability and have been related to environmental stress tolerance (Storz and Hengge, 2011). The high abundance of secondary metabolism genes (Q) together with the low number of genes associated with transcription (K) in the filter samples is consistent with another study in which these two categories differentiated oligotrophic from copiotrophic microorganisms (Lauro et al, 2009). The abundance of transposases in the RSF metagenomes was striking: they accounted for 1.18% ± 0.09% and 1.49% ± 0.04% of the total annotated genes in the ISLBulk and ISLTop, respectively, substantially higher than in a study of 2137 complete genomes where the average transposase abundance was 0.83% (Aziz et al, 2010).…”
Section: Metagenomic Assembly and Taxonomysupporting
confidence: 90%
“…Recent metagenomic sequencing of natural environments has revealed that microbial communities act in different trophic levels (Lauro et al, 2009), exhibit successional change (Koenig et al, 2011;Teeling et al, 2012;Huws et al, 2016) and engage in fierce competition when resources are limited (Weckx et al, 2011). This suggests that adaptation to specific niches must also occur in microbial communities, however demonstrating this in natural communities remains a challenge (Marco, 2008).…”
Section: Introductionmentioning
confidence: 99%